Press conference «Nutritional care in COVID-19» - E. O. Girutskaya (Лечащий Врач)
In February 2021, an online press conference entitled «Nutritional care in COVID-19» was held. It presented the results of a prospective, open-label, comparative observational study evaluating the effect of specialty food mix on the ability of COVID-19 patients to recover. The study was conducted under the auspices of the National Association for Clinical Nutrition and Metabolism at 5 centers in Moscow, St. Petersburg, Yekaterinburg and Omsk. According to its results, nutritional support should be added to the standard methods of patient management: about 60-70% of patients with COVID-19 need specialized nutrition.